Genome‐wide Association Analysis of Ten Chilling Tolerance Indices at the Germination and Seedling Stages in Maize. Issue 8 (11th August 2013) - Huang, Juan; Zhang, Jianhua; Li, Wenzhen; Hu, Wei; Duan, Lichao; Feng, Yang; Qiu, Fazhan; Yue, Bing
Abstract Maize seedlings are very sensitive to chilling, especially during the transition phase from heterotrophic to autotrophic growth. Genetic dissection of the genetic basis of chilling tolerance would provide useful information for genetic improvement of maize inbreds. In this study, genome‐wide association analysis was conducted to explore the genetic architecture of maize chilling tolerance at the seed germination and seedling stages with an association panel of 125 inbreds. Ten tolerance indices (ratios of the performance of 10 germination rates and seedling growth‐related traits under chilling stress and control conditions) were investigated to assess the ability of chilling tolerance of the inbreds, and a total of 43 single nucleotide polymorphisms associated with chilling tolerance were detected, with none of them being related to chilling tolerance at both the germination and seedling stages simultaneously. Correlation analysis also revealed that the genetic basis of chilling tolerance at the seed germination stage is generally different from that at the seedling stage. In addition, a total of 40 candidate genes involving 31 of the 43 single nucleotide polymorphisms were predicted, and were grouped into five categories according to their functions. The possible roles of these candidate genes in chilling tolerance were also discussed.